U-series and ESR/U-series dating of the Stegodon–Ailuropoda fauna at Black Cave, Guangxi, southern China with implications for the timing of the extinction of Gigantopithecus blacki. (1st April 2017) - Shao, Qingfeng; Wang, Yuan; Voinchet, Pierre; Zhu, Min; Lin, Min; Rink, William Jack; Jin, Changzhu; Bahain, Jean-Jacques
Abstract: Gigantopithecus blacki was once a common primate during Early Pleistocene, distributed throughout southern China, but then it gradually declined with time and finally became extinct probably during Middle Pleistocene. Black Cave in Guangxi (the Zhuang Nationality Autonomous Region) was the first site yielding G. blacki teeth in-situ in 1956. It also produced numerous mammalian fossils belonging to the typical Middle Pleistocene Stegodon–Ailuropoda fauna from sediments overlying the G. blacki level. The present study carried out coupled ESR/U-series dating study of five Bovidae teeth from this palaeontological layer and obtained a weighted mean age of 383 ± 20 ka for this Stegodon–Ailuropoda fauna. This age estimate on fossil teeth is constrained by two 230 Th/U ages of 404 ± 24 ka and 382 ± 9 ka obtained on speleothems formed below and above the level of the Stegodon–Ailuropoda fauna. The Black Cave Stegodon–Ailuropoda fauna can be therefore correlated with MIS 11, and the remains of G. blacki should be older than 400 ka.